1999
DOI: 10.1038/sj.onc.1203102
|View full text |Cite
|
Sign up to set email alerts
|

Protein stabilization: a common consequence of mutations in independently derived v-Myc alleles

Abstract: Myc is overexpressed in many cancers as a result of gene rearrangement or ampli®cation, but coding sequence changes which cluster in the N-terminal transactivation domain also appear to play a role in tumour progression. The prototypic v-Myc gene of MC29 virus diers from avian c-Myc by a series of mutations, including a change at a regulatory phosphorylation site within the mutational hotspot (thr-61) which is known to potentiate transformation in vitro. We now show that the mutation at thr-61 stabilizes the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
18
1
Order By: Relevance
“…Our data con®rm results of others that increased Myc stability in the cell is related to transforming ability (Gavine et al, 1999;Salghetti et al, 1999). However, we found that the di erences in Gag-Myc protein half-lives were not re¯ected in the steady state levels ( Figure 6).…”
Section: Discussioncontrasting
confidence: 34%
See 4 more Smart Citations
“…Our data con®rm results of others that increased Myc stability in the cell is related to transforming ability (Gavine et al, 1999;Salghetti et al, 1999). However, we found that the di erences in Gag-Myc protein half-lives were not re¯ected in the steady state levels ( Figure 6).…”
Section: Discussioncontrasting
confidence: 34%
“…v-Myc was shown to be three times more stable than c-Myc, but with a 61Met-4Thr backmutation, v-Myc was degraded in the same time frame as c-Myc with a half life of 20 ± 30 min (Gavine et al, 1999;Hann and Eisenman, 1984). v-Mycs from MH2 and T17, a feline myc-transducing retrovirus, were also more stable than c-Myc (Gavine et al, 1999).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations